2016
DOI: 10.1136/annrheumdis-2015-208980
|View full text |Cite
|
Sign up to set email alerts
|

How well do ACPA discriminate and predict RA in the general population: a study based on 12 590 population-representative Swedish twins

Abstract: Presence of ACPA and especially high titres of anti-CCP2 have a high diagnostic accuracy for an RA diagnosis in a population setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 52 publications
0
44
1
Order By: Relevance
“…7 It is logical to hypothesise that each of these aims can be facilitated by the identification and development of appropriate biomarkers. However, while peripheral blood biomarkers such as rheumatoid factor and anti-citrullinated peptide antibodies (ACPA) have been shown to be relatively specific and may predict development of RA in asymptomatic individuals, 8,9 they may only be found in 70-80% of RA subjects. Indeed, beyond these factors our repertoire of blood biomarkers to assist with diagnosis, disease progression and response to therapy is currently extremely limited.…”
Section: General Considerationsmentioning
confidence: 99%
“…7 It is logical to hypothesise that each of these aims can be facilitated by the identification and development of appropriate biomarkers. However, while peripheral blood biomarkers such as rheumatoid factor and anti-citrullinated peptide antibodies (ACPA) have been shown to be relatively specific and may predict development of RA in asymptomatic individuals, 8,9 they may only be found in 70-80% of RA subjects. Indeed, beyond these factors our repertoire of blood biomarkers to assist with diagnosis, disease progression and response to therapy is currently extremely limited.…”
Section: General Considerationsmentioning
confidence: 99%
“…We thank Bossuyt1 for his letter and the comments related to our previous published study 2. We agree that the calculated test likelihood ratios for low-positive anticitrullinated protein antibody (ACPA) reflect the relative uncommonness of low-titre ACPA in prevalent rheumatoid arthritis (RA) (despite a significant association between).…”
mentioning
confidence: 70%
“…Hensvold et al 1 reported on the discriminatory capacity of anticitrullinated protein antibodies (ACPA) for diagnosing rheumatoid arthritis (RA) 1. A major strength of the study is that it was performed in a population setting and that a large number of controls (n=12 434) were included, thereby allowing a reliable estimate of the specificity of ACPA.…”
mentioning
confidence: 99%
“…The unique and large dataset presented by Hensvold et al 1 allows to deduce test-result interval specific LRs. The LRs are 0.35 (95% CI 0.28 to 0.43), 3.4 (95% CI 1.5 to 7.5) and 73.6 (95% CI 58.7 to 92.3) for an anti-CCP2 test result <25 AU/mL, between 25 and 75 AU/mL and ≥75 AU/mL, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation